An Unprecedented Cyclization Mechanism in the Biosynthesis of Carbazole Alkaloids in Streptomyces. Issue 38 (13th August 2019) - Kobayashi, Masaya; Tomita, Takeo; Shin‐ya, Kazuo; Nishiyama, Makoto; Kuzuyama, Tomohisa
Abstract: Carquinostatin A (CQS), a potent neuroprotective substance, is a unique carbazole alkaloid with both an ortho ‐quinone function and an isoprenoid moiety. We identified the entire gene cluster responsible for CQS biosynthesis in Streptomyces exfoliatus through heterologous production of CQS and gene deletion. Biochemical characterization of seven CQS biosynthetic gene products (CqsB1–7) established the total biosynthetic pathway of CQS. Reconstitution of CqsB1 and CqsB2 showed that the synthesis of the carbazole skeleton involves CqsB1‐catalyzed decarboxylative condensation of an α‐hydroxyl‐β‐keto acid intermediate with 3‐hydroxybutyryl‐ACP followed by CqsB2‐catalyzed oxidative cyclization. Based on crystal structures and mutagenesis‐based biochemical assays, a detailed mechanism for the unique deprotonation‐initiated cyclization catalyzed by CqsB2 is proposed. Finally, analysis of the substrate specificity of the biosynthetic enzymes led to the production of novel carbazoles. Abstract : Magnificent seven : The total biosynthetic pathway of the carbazole alkaloid carquinostatin A (CQS) was established through biochemical characterization of seven CQS biosynthetic gene products CqsB1–7. The crystal structure of CqsB2, which catalyzes the cyclization step, provides mechanistic insights into the intricate reactions involved in the enzymatic synthesis of carbazoles.